COVID-19 and the calls of humanistic social work: exploring the developmental-clinical social work concerns of the pandemic - Chigangaidze, Robert K. (SAGE Publications, 2022)
Any health outbreak is beyond the biomedical approach. The COVID-19 pandemic exposes a calamitous need to address social inequalities prevalent in the global health community. Au fait with this, the impetus of this article is to explore the calls of humanistic social work in the face of the pandemic. It calls for the pursuit of social justice during the pandemic and after. It also calls for a holistic service provision, technological innovation and stewardship. Wrapping up, it challenges the global community to rethink their priorities – egotism or altruism. It emphasizes the ultimate way forward of addressing the social inequalities.